Distance learning challenges which was faced mothers to educate their children in light of the Corona crisis in the Jordanian governorate of Aqaba for the academic year 2020/2021 - AlQuabe'h, Wafa' Abdulrahim (Journal of Educational and Psychological Sciences, 2022)
This study aimed at identify difficulties that mothers face in distance education during the Corona period. Where the study was keen to monitor the experience of mothers during this difficult circumstance in order to be able to take the right measures that would develop appropriate solutions to meet their needs. The study included (150) mothers who were chosen at random as mothers of students studying in different schools, including public and private, in the Aqaba Governorate in Jordan, and they participated in this study voluntarily. Where the descriptive approach was applied to collect and analyze data. The opinions of mothers of children and students in different stages of education, whether primary, intermediate or secondary, were surveyed. The data was collected using a questionnaire designed by (Qualtrics) platform to serve the research topic, achieve its objectives and answer its questions. The results of the study revealed many challenges that mothers faced while teaching their children, the most important of which is the difficulty of dealing with some educational programs and the lack of skills in using modern technological technologies.Accordingly, this study presented some golden recommendations that would improve and enhance the quality of education and ensure the achievement of the maximum cognitive skills of the student, including the development of technical skills for mothers and students alike to meet the requirements of the current and future era and some recommendations related to the need to reorganize and manage laws and policies relating to working women in a manner that supports their social conditions.
Keywords: distance education; Corona pandemic; schools; mothers; Jordan; Aqaba Governorate